Viral infection triggers interferon-induced expulsion of live Cryptococcus neoformans by macrophages. - Paula I Seoane; Leanne M Taylor-Smith; David Stirling; Lucy C K Bell; Mahdad Noursadeghi; Dalan Bailey; Robin C May (PLoS Pathogens, 2020)
Cryptococcus neoformans is an opportunistic human pathogen, which causes serious disease in immunocompromised hosts. Infection with this pathogen is particularly relevant in HIV+ patients, where it leads to around 200,000 deaths per annum. A key feature of cryptococcal pathogenesis is the ability of the fungus to survive and replicate within the phagosome of macrophages, as well as its ability to be expelled from host cells via a novel non-lytic mechanism known as vomocytosis. Here we show that cryptococcal vomocytosis from macrophages is strongly enhanced by viral coinfection, without altering phagocytosis or intracellular proliferation of the fungus. This effect occurs with distinct, unrelated human viral pathogens and is recapitulated when macrophages are stimulated with the anti-viral cytokines interferon alpha or beta (IFNα or IFNβ). Importantly, the effect is abrogated when type-I interferon signalling is blocked, thus underscoring the importance of type-I interferons in this phenomenon. Lastly, our data help resolve previous, contradictory animal studies on the impact of type I interferons on cryptococcal pathogenesis and suggest that secondary viral stimuli may alter patterns of cryptococcal dissemination in the host.